Thermodynamic Excess Properties of Binary Mixtures of Acetyl acetone and Ethyl Acetate - Al-abbasi, Aisha; Izriq, Raja (Journal of Pure & Applied Sciences, 2022)
The density (ρ), viscosity (η), surface tension (σ), and refractive index (R) of binary mixtures of acetylacetone (acac) with ethyl acetate (Etac) were determined at atmospheric pressure over the entire composition range of mixtures. The values of mixtures and pure liquids have been used to calculate the excess volume (VE), deviation in viscosity (Δη), and deviation in surface tension. The computed results were fitted to the Redlich–Kister polynomial equation. The excess molar volume (VE) for the binary system investigated exhibits a positive deviation at 298.15 K, and the positive deviation at 303.15 K becomes too negative as the mole fraction Xacac increases. The deviation in viscosity (Δη) and deviation in surface tension (Δσ) show negative values from the ideality at 303.15 The negative magnitude suggests the presence of strong intermolecular interactions between unlike molecules in the binary mixtures.